2017
DOI: 10.2147/jir.s93797
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of STAT proteins by recombinant human IL-6 in immortalized human chondrocyte cell lines, T/C28a2 and C28/I2

Abstract: Two immortalized human juvenile chondrocyte cell lines, T/C28a2 and C28/I2, were employed to determine the extent to which recombinant human (rh) IL-6, a known cytokine activator of the Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway in many cell types, caused STAT proteins to be phosphorylated. The results showed that STAT3 was constitutively phosphorylated in the absence of rhIL-6 in T/C28a2 chondrocytes. However, C28/I2 chondrocytes treated with rhIL-6 caused STAT1, STAT3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…We also showed western blots at Immunology summit-2015 demonstrating that STAT1 was constitutively phosphorylated in the T/C28a2 chondrocyte line [ 16 ]. However, C-28/I2 chondrocytes incubated with rhIL-6 (50 ng/ml) resulted in the phosphorylation of STAT3 without changing total STAT3 [ 15 ]. Moreover, the combination of rhIL-6 and the pan-JAK-small molecule inhibitor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also showed western blots at Immunology summit-2015 demonstrating that STAT1 was constitutively phosphorylated in the T/C28a2 chondrocyte line [ 16 ]. However, C-28/I2 chondrocytes incubated with rhIL-6 (50 ng/ml) resulted in the phosphorylation of STAT3 without changing total STAT3 [ 15 ]. Moreover, the combination of rhIL-6 and the pan-JAK-small molecule inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…U0126, a small molecule inhibitor of MEK1/2, an upstream protein kinase required for the phosphorylation of ERK1/2 was purchased from Cell Signaling Technology. The Signal Transducer and Activator of Transcription-3 (U-STAT3) antibodies were purchased from R&D Systems and the β-actin antibody from Cell Signaling Technology [ 15 ]. An antibody which interacts with human neutrophil gelatinase-associated lipocalin (NGAL) was purchased from Pierce Biotechnology [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of synovial fluids and sera from RA and OA patients with active disease showed that these samples contained significantly elevated levels of various pro-inflammatory cytokines and growth factors when compared to a control group [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68]. Of note, incubation of rat [69], non-arthritic or human chondrocytes from OA cartilage [70][71][72][73][74][75][76] or immortalized lines of human chondrocytes [77] with physiological levels of these cytokines, growth factors (e.g., VEGF and FGF) or additional soluble mediators (e.g., nitric oxide) were shown to induce apoptosis, which was accompanied by activation of SAPK/MAPK, JAK/STAT or PI3K/Akt/mTor signaling in these cells [78][79][80][81]. In addition, mediators of inflammation, including prostaglandin E 2 and neuropeptides (e.g., Substance P), are also implicated in perpetuating chronic inflammation [38].…”
Section: Compelling Evidence That Many Factors Relevant To Ra and Oa mentioning
confidence: 99%
“…The results of experimental studies cited in Refs. [70,72,77,80] were supported in part by grants from the National Institutes of Health, Takeda Pharmaceuticals of North America and Genentech/Roche Group.…”
Section: Acknowledgementsmentioning
confidence: 99%